THE EFFECT OF WORKLOAD, COMPENSATION, AND CAREER DEVELOPMENT ON THE PERFORMANCE OF EMPLOYEES OF THE PUBLIC WORKS AND HOUSING AGENCY OF ANAMBAS ISLANDS REGENCY WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Wan Iwan Darmawan; Chablullah Wibisono; Sri Yanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the effect of workload, compensation, and career development on job satisfaction and performance of employees at the Public Works and Public Housing Agency of the Anambas Islands Regency. The research method used a quantitative approach with saturated sampling techniques on 163 employees consisting of 122 men (74.8%) and 41 women (25.2%). Data were collected through a questionnaire using a Likert scale and analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results showed that of the 10 hypotheses tested, 7 were accepted and 3 were rejected. Workload had a significant positive effect on job satisfaction (β=0.377; p=0.018), compensation had a significant positive effect on job satisfaction (β=0.311; p=0.022), but career development did not have a significant effect on job satisfaction (β=0.301; p=0.084). Career development has a significant positive effect on employee performance (β=0.305; p=0.000), while workload and compensation do not have a direct effect on employee performance. Job satisfaction has a very significant effect on employee performance with the highest coefficient (β=0.778; p=0.000). Mediation analysis shows that workload (β=0.293; p=0.011) and compensation (β=0.242; p=0.025) affect employee performance through job satisfaction, but career development does not mediate through job satisfaction. This study confirms that job satisfaction is the main predictor of employee performance, so organizations need to prioritize strategies to increase job satisfaction through the optimization of challenging workloads, improvements to the compensation system, and the revitalization of career development programs to optimize employee performance in public services in the fields of infrastructure and spatial planning.